PEMBELAJARAN PEMASARAN ONLINE, SELF EFFICACY DAN MINAT BERWIRAUSAHA ONLINE KELAS XI PEMASARAN SMK NEGERI SURAKARTA - Fadhilah, Shofiana; Wahyuni, Sri; Nugroho, Jonet Ariyanto (Department of Economics Education, Universitas Sebelas Maret, 2016)
This research aimed to find out whether or not there was an effect of (1) online marketing learning and self-efficacy factors to the online entrepreneurship interest on XI-grade Marketing skill competency in SMK Negeri Surakarta City; (2) online marketing learning factor to the online entrepreneurship interest on XI-grade Marketing skill competency in SMK Negeri Surakarta City; and (3) self efficacy factor to the online entrepreneurship interest on XI-grade Marketing skill competency in SMK Negeri Surakarta City.The population of research was the students of SMK Negeri Surakarta. The sample consisted of 135 students taken using Isaac and Michael’s formula. The sampling technique used was proportional random sampling with lottery. This research method used is quantitative method with a descriptive design. Technique of collecting data used was questionnaire. Technique of analyzing data used was a multiple regression. Significance level used in this research was 0.05.The results of research were as follows. Firstly, there was a positive significant effect of online marketing learning and self-efficacy factors on the online entrepreneurship interest of students with the test result of Fstatistic > Ftable (5.816 > 3.065) at significance level of 0.05 with regression equation Y = 27.345 + 0.189X1 + 0.215X2. Secondly, there was a positive significant effect of online marketing learning factor on the online entrepreneurship interest of students with probability value < 0.05 (0.031 < 0.05) and tstatistic > ttable (2.177 > 1.979). Thirdly, there was a positive significant effect of self-efficacy factor on the online entrepreneurship interest of students with probability value < 0.05 (0.024 < 0.05) and tstatistic > ttable (2.278 > 1.97). The coefficient of determinacy (R2) was 0.081 or 8.1%.